An overview of seismic hybrid testing of engineering structures. (1st July 2016) - McCrum, D.P.; Williams, M.S.
Highlights: Development of the pseudo dynamic test method to the current hybrid test method. Summary of developments in accuracy and stability of the software. Summary of developments in accuracy and stability of the hardware. Summary of developments in geographically distributed hybrid testing. Summary of applications of pseudo dynamic and real-time hybrid testing. Abstract: An overview of research on the development of the hybrid test method is presented. The maturity of the hybrid test method is mapped in order to provide context to individual research in the overall development of the test method. In the pseudo dynamic (PsD) test method, the equations of motion are solved using a time stepping numerical integration technique with the inertia and damping being numerically modelled whilst restoring force is physically measured over an extended timescale. Developments in continuous PsD testing led to the real-time hybrid test method and geographically distributed hybrid tests. A key aspect to the efficiency of hybrid testing is the substructuring technique where the critical structural subassemblies that are fundamental to the overall response of the structure are physically tested whilst the remainder of the structure whose response can be more easily predicted is numerically modelled. Much of the early research focused on developing the accuracy and efficiency of the test method, whereas more recently the method has matured to a level where the test method is applied purely as a dynamic testing technique. Developments in numerical integration methods, substructuring, experimental error reduction, delay compensation and speed of testing have led to a test method now in use as full-scale real-time dynamic testing method that is reliable, accurate, efficient and cost effective.